Research on the risk assessment of the power grid enterprises’ agency power purchase business in China: A hybrid multi-attribute decision-making framework based on FUCOM-F and GRA-MARCOS - Gan, Yue; Zheng, Chaofeng; Chu, Baoju; Li, Jianfang; Zhang, Yuanyuan; Jia, Yixin (Frontiers in Energy Research, 2024)
To steadily promote the reform of sales electricity prices, China has innovatively proposed to carry out grid enterprises agency power purchase business (GEAPPB) as a transitional scheme for industrial and commercial users to enter the power market in the future. However, the GEAPPB covers a wide range of users and involves complex business processes, the risks throughout the process of the GEAPPB will affect the organization and operation of the business, this paper proposes a GEAPPB risk assessment technique. Firstly, a risk evaluation index system containing 10 indicators is designed based on the characteristics and development process of GEAPPB; Secondly, a risk assessment model based on FUCOM-F and grey relational analysis (GRA) improved MARCOS is constructed; Finally, 7 grid enterprises in China are taken as examples to verify the validity and scientificity of the model. The results show that improving the accuracy of power forecasting, optimizing the agency power purchase strategy, and strengthening the demand response management are the key schemes to reduce the risk of GEAPPB. Compared with the other 3 evaluation models, the proposed model has good applicability and effectiveness for the risk evaluation of GEAPPB.